Functional assessment in left ventricular non-compaction cardiomyopathy in multimodality imaging era might improve the definition - Ionela Simona Visoiu; Roxana Cristina Rimbas; Loredana Gheorghiu; Ruxandra Dragoi Galrinho Antunes Guerra; Alina Ioana Nicula; Dragos Vinereanu (Sciendo, 2021)
Left ventricular non-compaction (LVNC) is an increasingly recognized phenotype. The current definition of the LVNC does not mention LV dysfunction as an absolute criterion in addition to morphological criteria. LV dilatation and decreased LV ejection fraction (LVEF) are often late manifestations of the disease and correlate with the occurrence of cardiovascular complications. However, to define LVNC as a cardiomyopathy, functional criteria must be fulfilled, in addition to the morphological ones. Multimodality imaging, such as myocardial deformation and myocardial work analysis derived from speckle tracking echocardiography (STE), in combination with cardiac magnetic resonance (CMR) might improve diagnosis and characterization of non-compaction, exposing earlier signs of LV systolic dysfunction. We present two comparative cases of LVNC in order to highlight the idea of subclinical dysfunction even in apparently benign forms with preserved LVEF, and also the importance of multimodality imaging approach.